Signaling Pathways in Developing and Pathological Tissues and Organs of the Craniofacial Complex - Thimios Mitsiadis (Frontiers Research Topics, 2018)
Head formation requires the well-orchestrated and harmonised development of various tissues and organs within the craniofacial complex. A big variety of signaling pathways are involved in this process by controlling cell proliferation, migration, differentiation, tissue morphogenesis, homeostasis and regeneration. Deregulation and malfunction of these signaling molecules may lead to mild or severe craniofacial pathologies. This eBook is a collection of articles dealing with a variety of important signals involved in the control of developmental and pathological events of craniofacial organs and tissues. These recent advances show the importance of signaling pathways in craniofacial physiology and pathology and generate important new knowledge aiming the development of new pharmaceutical products that mimic and/or block the actions of specific molecules.